2017
DOI: 10.5217/ir.2017.15.4.434
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence in inflammatory bowel disease

Abstract: Inflammatory bowel disease (IBD) is a chronic idiopathic inflammatory condition with intestinal and extraintestinal manifestations. Medications are the cornerstone of treatment of IBD. However, patients often adhere to medication poorly. Adherence to medications is defined as the process by which patients take their medications as prescribed. Treatment non-adherence is a common problem among chronic diseases, averaging 50% in developed countries and is even poorer in developing countries. In this review, we wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
114
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(119 citation statements)
references
References 60 publications
3
114
1
1
Order By: Relevance
“…This finding has critical clinical implications for adherence monitoring and management. First, in contrast to the majority of previous IBD adherence studies, which have utilised a consensus cut‐point and classify non‐adherence as <80% the current study showed that when adherence fell below 86%, the likelihood of treatment escalation significantly increased. Second, the two adherence trajectories did not diverge until month 6, indicating the importance of continued assessment of adherence over at least the first 6 months following diagnosis in order to identify whether adherence is deteriorating and the likelihood that adherence may be a factor in the need for treatment escalation.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This finding has critical clinical implications for adherence monitoring and management. First, in contrast to the majority of previous IBD adherence studies, which have utilised a consensus cut‐point and classify non‐adherence as <80% the current study showed that when adherence fell below 86%, the likelihood of treatment escalation significantly increased. Second, the two adherence trajectories did not diverge until month 6, indicating the importance of continued assessment of adherence over at least the first 6 months following diagnosis in order to identify whether adherence is deteriorating and the likelihood that adherence may be a factor in the need for treatment escalation.…”
Section: Discussioncontrasting
confidence: 99%
“…Given the emphasis on achieving optimal nutrition, growth and development in this population, treatment escalation from 5‐ASA is often indicated to promote mucosal healing and avoid steroid dependence. Despite these advances in treatment, compared to adults, the rate of surgical needs in youth with UC remains higher, which may be indicative of continued difficulties with adherence to immunomodulators or biologic medications as reported in the literature . As such, it is important for providers to recognise and intervene around non‐adherence whether the patient is on maintenance therapy or another type of therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to grouping discontinued and not adherent group together, we were unable to generate meaningful results on other adverse pregnancy outcomes, such as stillbirth and small‐for‐gestational age infants (10th percentile) due to the small number of events. Lastly, our definition for adherence to medication while valid, overestimates medication adherence as it assumes that the prescription dispensed matched the patient's consumption; it does not account for patients who may potentially consume less than what is dispensed from community pharmacies …”
Section: Discussionmentioning
confidence: 99%